LEGALITAS PERJANJIAN JUAL BELI MELALUI E-COMMERCE SECARA ONLINE MELALUI FITUR TAWAR MENAWAR YANG MERUGIKAN PIHAK PENJUAL - Bodhi Alivian; Raissa Arlyn Manikam (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2022)
The act of buying and selling is a common thing in society, in its development buying and selling can not only be carried out face-to-face, but with the development of technology and information, these activities can be carried out through online market applications. With this development, to attract public interest in the application, various features were added with a hope that these features could attach the community interest in online buying and selling activities. One of the features provided is the bargaining feature, where the seller and buyer can negotiate the price until a certain point that has been agreed by both parties. However, in practice, many irresponsible parties misused this feature by taking advantage of the negligence of one other party, in this case the seller was the victim and by this action the seller was aggrieved in economic terms. Therefore, this journal will discuss the legality of the sale and purchase agreement which occurred based on the negligence of a party that aggrieves the seller in the online market by using the bargaining feature.